Life Skills : Predictors of Well-being among School Going Students - Seth, Alka; Sharma, Novrattan (INDIAN EDUCATIONAL REVIEW, 2020)
Promotion of mental health includes the growth of psychological resources including improvement in quality of life, preventing mental disorders and increasing satisfaction and happiness. In today’s world of stress and competition, students are required to imbibe some kind of skills, which can enhance their well-being and mental health and enable them to adapt and get the right direction in life. Well-being for life lies in feeling comfortable, healthy and happy. Present study takes into account the role of life skills in predicting well-being among adolescents. A group of 300 adolescents with an age range of 12–16 years from a CBSE affiliated school of Kaithal district in Haryana formed the sample of study. Tools used for present study were Life Skills Assessment Scale and Well-being Manifestation Scale. Results of the study showed high correlation between well-being and different components of life skills. The regression analysis of data showed that different variables of life skills were significant predictors of well-being of students. The study has implications in terms of organising programmes on training of life skills for students in schools. The study also emphasises on the development of modules of life skills for adolescents.